2010
DOI: 10.1007/s10681-010-0321-x
|View full text |Cite
|
Sign up to set email alerts
|

Seedling salt tolerance in tomato

Abstract: Soils with higher concentrations of salt are becoming more and more a constraint for many crops to obtain high yields. Wild tomato species, adapted to adverse environments, are a potential reservoir for genes underlying quantitative trait loci (QTL) related to salt tolerance in tomato. In this study two introgression line (IL) libraries derived from two different wild species, Solanum pennellii LA716 and Solanum lycopersicoides LA2951, were used to identify QTLs for salt tolerance in the seedling stage. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…There is evidence that the genetic basis of salt tolerance in crop plants is complex involving heterotic, dominant, semi-dominant, additive, non-additive, and epistatic effects (Flowers 2004;Li et al 2011). Monforte et al (1997) reported that salt tolerance in S. pimpinellifolium accessions (L1 and L5) is characterized by higher fruit number, total fruit weight and mean fruit weight under saline condition, which is controlled by several QTLs with epistatic and heterotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the genetic basis of salt tolerance in crop plants is complex involving heterotic, dominant, semi-dominant, additive, non-additive, and epistatic effects (Flowers 2004;Li et al 2011). Monforte et al (1997) reported that salt tolerance in S. pimpinellifolium accessions (L1 and L5) is characterized by higher fruit number, total fruit weight and mean fruit weight under saline condition, which is controlled by several QTLs with epistatic and heterotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Increment in saline areas is due to low rainfall, high evaporation, native rocks, saline irrigation water, poor water management and disproportionate use of chemical fertilizers (Dasgan et. al., 2002;Mahajan and Tuteja, 2005;Li et. al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although much research has been conducted to examine the effects of soil salinity on halophytic plant species (Ungar, 1991), more recent research has focused on salt tolerance among food crops, including chili peppers (van der Beek and Ltifi, 1991) and tomatoes (Li et al, 2011), two closely related members of the Solanaceae.…”
Section: Introductionmentioning
confidence: 99%